Social Work as a Profession - Monisha, S. (2017)
Social work is a discipline within human services. Its main goal is to assist individuals and families with their needs and solve their problems using a multidiscipline approach. In order to be effective, social workers work closely with many agencies and professionals. Social work is usually a part of the Human Services Department of a government. It serves as a link between the government’s clients and other government resources, such as: manpower training leading to employment, welfare payments towards financial assistance, legal consultation in dealing with legal problems, food and water relief at times of drought, famine and war, etc. As a social worker, you will also work closely with medical professionals in order to provide medical care for clients; with school personnel to identify children who are in need of help and with counselors and psychologists in order to provide psychological counseling. Today the problems faced by individuals and families are often complicated, and assistance from many agencies is needed.Professional social workers assist individuals, groups, or communities to restore or enhance their capacity for social functioning, while creating societal conditions favorable to their goals. The practice of social work requires knowledge of human development and behavior, of social, economic and cultural institutions, and of the interaction of all these factors. Keywords: Social Work, Human Service Department, Human Development, Professio